Les premiers pas du Réseau thématique Ethnoécologie et interactions humains-écosystèmes - Sandrine Gallois; Richard Raymond (Revue d'ethnoécologie)
We present a short report of the first day of the French Ethnoecology and Humans-Ecosystems Interactions Thematic Network. This thematic network is contextualized alongside the thematic school that preceded it and the European Network of Ethnobiology, which is being built in parallel. These initiatives strengthen the position of Ethnoecology in France and Europe, highlighting its relevance in addressing social and environmental crises.